The Jesus handbook - Schröter, Jens; Jacobi, Christine; Brawley, Robert L. (William. B. Eerdmans Publishing Company, 2022)
"An international collection of scholarship on Jesus of Nazareth, his world, the outcomes of his life, and the quest to locate him in historical context"--